Analisis Perilaku Konsumen Dalam Mengkonsumsi Beras Anak Daro (Studi Kasus pada Perumahan Pandau Permai Kabupaten Kampar) - Oktiadi, Chrisda; Tety, Ermi; ', Rosnita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The research was conducted in Pandau Permai Housing Complex Kampar Regency, for 5 mounth start from April until August 2013. Respondents was 99 people and selected by purposive sampling. The study aims to determine consumer behavior in consuming anak daro rice by analyzing consumer attitudes and subjective norms. The method of analysis used in this study refers to analytical techniques in the reasoned action theory by Fishbein. The result depict that consumer attitudes in consuming anak daro rice show the positive value upon attributes brand, price, taste, cleanliness, color, texture or shape and the ease of obtaining attribute, while aroma attributes shows the negative value. The highest value of the attribute is taste attribute. Consumer’s subjective norm in consuming anak daro rice shows that attributes of income rate and attributes of people-surrounding gain the positive value, and attributes of people- surrounding gains the highest score. Consumer behavior in consuming anak daro rice shows the results that consumer interest in consuming anak daro rice is quite high. Cartesian diagram was used to analyze the rate of consumer confidence and interest in consuming anak daro rice. The result of the Cartesian diagram is, there is no attribute of anak daro rice in quadrant I (The Top Priority). In quadrant II (Maintain Achievement) there are attributes of taste, brand, price and cleanliness of the anak daro rice, for quadrant III (Low Priority) there are attributes of color and aroma of anak daro rice and there are attributes texture or shape and ease in obtaining of anak daro in quadrant IV (Excessive). Keywords: Consumer, Behavior, Attribute, Anak daro rice, Fishbein.